Surveillance on schistosomiasis in five provincial-level administrative divisions of the People's Republic of China in the post-elimination era - Jing-Yi Guo; Jing Xu; Li-Juan Zhang; Shan Lv; Chun-Li Cao; Shi-Zhu Li; Xiao-Nong Zhou (BMC, 2020)
Abstract Background The People's Republic of China (P. R. China) has made significant progress on schistosomiasis control. Among the 12 provincial-level administrative divisions (PLADs) with schistosomiasis endemic in P. R. China, Guangdong, Shanghai, Fujian, Guangxi and Zhejiang PLADs (following as five PLADs) had successively eliminated schistosomiasis during 1985-1995. However, consolidation of the schistosomiasis elimination in these five PLADs remains challenging. In the current study, we sought to understand the epidemic situation in these post-elimination areas and their surveillance capabilities on schistosomiasis. Methods Annual data reflecting the interventions and surveillance on human beings, cattle and snails based on county level from 2005 to 2016 were collected through the national schistosomiasis reporting system and the data were analyzed to understand the epidemic status of schistosomiasis in the five PLADs. A standardized score sheet was designed to assess the surveillance capacity for schistosomiasis of selected disease control agencies in five PLADs and ten counties. Assessment on surveillance capacity including schistosomiasis diagnostic skills, identification of snails' living and infection status and knowledge about schistosomiasis and its control were made. Descriptive analysis was used to analyze the epidemic status and evaluation results on surveillance capacities. Results The assessments showed that no local cases in humans and cattle or infected snail were found in these five PLADs since 2005. However, from 2005 to 2016, a total of 221 imported cases were detected in Zhejiang, Shanghai and Fujian, and 11.98 hm2 of new snail habitats were found in Zhejiang, Shanghai and Guangxi. In addition, snail infestation reoccurred in 247.55 hm2 of former snail habitats since 2011. For the surveillance capacity assessment, the accuracy rate of IHA and MHT were 100 and 89.3%, respectively. All participants could judge the living status of snails accurately and 98.1% on the infection status of snails. The accuracy rate of the questionnaire survey was 98.0%. Conclusions Elimination of schistosomiasis was consolidated successfully in five PLADs of P. R. China due to effective and strong post-elimination surveillance. Comprehensive consolidation strategies should be focused on the elimination of residual snails and the prevention of imported infection sources to consolidate the achievements of schistosomiasis control.